Endocarditis of the tricuspid valve associated with congenital coronary arteriovenous fistula - Ong, M. L. (BMJ Publishing Group, 1993)
A 17 year old girl with a congenital right coronary artery to coronary sinus fistula presented with recurrent septic pulmonary embolism secondary to tricuspid valve endocarditis. The diagnosis was made on the basis of echocardiography and cardiac angiography.